Pengaruh Kegiatan Practical Life Dalam Meningkatkan Kemandirian Anak Usia Dini Di TKS Aneuk Bangsa - Akmalia Faradis; Nurasiah Nurasiah; Dwhy Dinda (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This research is an experimental study with a One Group Pretest-Posttest Design conducted on children in group B1 at TKS Aneuk Bangsa in the 2024/2025 academic year. This research is motivated by the low independence of children in carrying out daily activities such as opening lunch boxes, putting on pants, and tidying up toys without teacher assistance. This low independence is caused by the habituation of Practical Life activities that have not been optimally implemented in schools. To increase children's independence, researchers implemented Practical Life activities as a form of learning that emphasizes the practice of daily living skills. The results of the study showed an increase in children's independence after being given treatment. The average pretest score showed that most children were not yet independent, whereas after being given Practical Life activities for three treatments, the posttest score increased significantly. Based on the results of the t-test and N-Gain calculations, the results showed that Practical Life activities had a positive effect on increasing the independence of early childhood children. In addition to quantitative improvements, qualitatively children became more confident, responsible, disciplined, and able to carry out daily activities independently. Thus, Practical Life activities have been proven effective in increasing the independence of early childhood children at TKS Aneuk Bangsa